Mediating mechanism of customer satisfaction on customer relationship management implementation and customer loyalty among consolidated banks - Adeiza, A.; Abdullahi, M.S.; Abdel Fattah, F.A.M.; Fawehinmi, O.; Ismail, N.A.; Arnaut, M.; Aigbogun, Osaro; Adam, I.S.; Ehido, A. (2022)
The aim of this study is to investigate the mediating mechanism of customer satisfaction (CS) on customer relationship management (CRM) and customer loyalty (CL) among Nigerian consolidated banks. This paper used a survey research design, and the study unit of analysis consists of selected customers among Nigerian consolidated banks. This study used a purposive sampling technique whereby structured questionnaires were used to collect data from 750 customers of the 5 focused banks in Kano State, Nigeria. Partial least square-structural equation modelling (PLS-SEM) was used to evaluate the study hypotheses. The outcome of the study revealed that CRM has a significant effect on CL while CS partially mediates CRM and CL relationship. This paper provides substantial results to practitioners to realize the role of developing a CRM strategy in the Nigerian banking industry. In line with that, the management of the banks should build sound CRM components such as process fit, customer information quality and information system support to deliver sound services in order to operate and compete in the banking ecosystem effectively. This paper has made a substantial contribution to the body of knowledge in the CS, CL, and CRM literature by operationalizing it within the Nigerian banking industry.